Self-initiated global mobility as a career project : analyzing time, gender and identity - Milani, Giovanna Silveira (2023)
This doctoral dissertation defends that self-initiated expatriation, as a boundaryless career project, expands the individual's initial field of possibilities, given the boundary crossing aspect of one geographically changing countries. When in the new context, reality will have to be renegotiated given the changes. The experimentation allowed by a different environment will trigger a reflection process that has a strong potential for metamorphosis. Throughout this process, the way the individual sees himself, the way he perceives time, and the way he responds/deals with gendered difficulties can change. The first chapter introduces the literature that supports the project and the author's research approach. The second chapter is an empirical paper addressing expatriation as a transformational experience with impact in the individuals' identity. The third chapter is a theoretical essay about time and career studies, exploring the possibilities for applications in contexts of crossing borders. The fourth chapter, another empirical study, discusses women's experience while engaging in careers abroad. From the analysis of the doctoral dissertation results it emerged that: the narratives of SIE as complex and multidimensional, with accounts of a transformed identity due to the move; international careers do not emerge automatically by crossing a border, but are formed throughout the life experiences one has access, and the meanings attributed to it by our temporal perceptions; that biographical and historical time will intervene in the pursuit of an international career; and that women can create opportunities by opting for unconventional careers while navigating boundaries in expatriation.